Annexin A1 downregulates in vitro IL-1β production in L. braziliensis-infected cells - Santos, Camila P.; Nascimento, Mauricio T.; Santana, Marina B.R.; Carvalho, Edgar M.; Carvalho, Lucas P. (Frontiers in Immunology, 2025)
Cutaneous leishmaniasis (CL) is an infectious disease characterized by severe local inflammatory response, predominantly mediated by cytokines such as IL-1β and TNF, and cytotoxicity, contributing to tissue damage and lesion development. Given the high rate of therapeutic failure in Leishmania braziliensis transmission areas, the investigation of molecules that regulate inflammatory response has become a promising adjuvant therapeutical strategy. In this study we investigated the effects of Annexin A1 (ANXA1) on the inflammatory response of CL patients. We initially performed in silico analyses from our previous transcriptome databases and found increased expression of ANXA1, IL1B, and IL10 genes in skin biopsies from CL patients when compared to healthy skin from healthy subjects (HS). Also, increased levels of ANXA1, IL1β, and IL10 proteins were observed in serum levels and cultures of skin biopsies in CL patients when compared to HS. Treatment of lesion biopsies with recombinant ANXA1 reduced IL-1β levels without affecting IL-10 secretion, indicating a selective anti-inflammatory effect. Additionally, monocyte-derived macrophages from HS increased ANXA1, IL-1β, and IL-10 production upon Leishmania infection. Blockade of FPR2 receptor increased ANXA1 levels. Finally, addition of recombinant ANXA1 to macrophages did not affect the ability of these cells to kill Leishmania. Our findings demonstrate that ANXA1 negatively regulates IL-1β in CL, without impairing anti-inflammatory mechanisms or macrophage microbicidal activity, highlighting its potential use as an adjuvant therapy for controlling inflammation and disease progression.